Peran Etnokonseling dalam Meningkatkan Pemahaman Budaya pada Anak Gen Z di Lembaga PAUD - Sakdiah, Eka; Rodiyati; Rapika Hidayu; Desi Arpa (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
The development of technology and globalization has changed the way children, particularly Generation Z, interact with the world around them. Children in this digital era are exposed to information from various cultures through social media and other digital platforms, making cultural understanding essential to help them comprehend their identities and appreciate diversity. This study aims to explore the role of ethnocounseling in enhancing cultural understanding among children in Early Childhood Education (ECE) institutions. The method used is a qualitative approach with a case study design, involving 30 children aged 4 to 6 years and 5 educators. Data were collected through observations, in-depth interviews, and curriculum document analysis. The results indicate that the implementation of ethnocounseling significantly improves children's cultural understanding, as well as their social skills and empathy. Children actively engage in activities that integrate cultural elements, such as folk tales and traditional games, which encourage interaction and discussion about diversity. Despite challenges in implementing ethnocounseling, such as a lack of training for educators, this study concludes that ethnocounseling can be an effective strategy for creating an inclusive learning environment that supports children's social and emotional development. Therefore, the application of ethnocounseling in ECE institutions is expected to help children grow into individuals who appreciate diversity and contribute positively to society.